Gingival Anaplastic Large-Cell Lymphoma Mimicking Hyperplastic Benignancy as the First Clinical Manifestation of AIDS: A Case Report and Review of the Literature - Rafaela Elvira Rozza-; Stefânia Jeronimo Ferreira; Diogo Lenzi Capella; Stephan Schwartz; Ana Helena Willrich; Lúcia de Noronha; Aline Cristina Batista Rodrigues Johann; Paulo Henrique Couto Souza (Hindawi Limited, 2013)
This paper presents an unusual case of gingival ALCL, which mimicked a benign hyperplastic lesion that occurred in a 57-year-old white man representing the first clinical manifestation of acquired immunodeficiency syndrome (AIDS). The patient was referred to the Dental Clinic of PUCPR complaining of a lobulated nodule on the gingiva of his upper central incisors. The presence of advanced chronic periodontitis and dental plaque raised suspicion for a benignancy. An excisional biopsy was performed, and large pleomorphic cells with an abundant cytoplasm, sometimes containing prominent nucleoli and "Hallmark" cells, were observed through hematoxylin and eosin staining. The tumor cells showed strong CD30 expression, EMA, Ki-67, and LCA, and negative stain for p80NPM/ALK, CKAE1/AE3, CD20, CD3, CD56, and CD15. The final diagnosis was ALCL (ALK-negative). Further laboratory tests revealed positivity for human immunodeficiency virus (HIV). The patient was submitted to chemotherapy, but four months after diagnosis, the patient died due to pneumonia and respiratory failure. Oral anaplastic large-cell lymphoma (ALCL) is a rare disorder. Only 5 cases involving the gingiva have been reported, and to our knowledge, this is the first case reported of the ALCL, which mimicked a hyperplastic benignancy as the first clinical manifestation of AIDS.